2016
DOI: 10.1159/000447964
|View full text |Cite
|
Sign up to set email alerts
|

Interest in Extended Release Naltrexone among Opioid Users

Abstract: Background/Aims: Treatment for addiction to illicit opioids has, thus far, been limited to 2 main approaches: maintaining physical dependence by administering opioids medically and medication-free abstinence with psychosocial support. Assisted abstinence by taking daily tablets with the opioid antagonist naltrexone is rarely practiced, but it is unclear whether this is due to the limited efficacy of this method or because of user opposition to antagonist medication. Therefore, we wanted to investigate opioid u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Previous studies have reported that many patients in OMT express a main goal of opioid abstinence (33,44,45). The before mentioned survey conducted by our research team, also discovered a high interest in XR-NTX treatment among OMT-patients (32). Since discontinuing substitution medication is risky even when patients are highly motivated, rather few succeed in detoxification from OMT and many relapse to opioid use (46).…”
Section: Retention In Treatmentmentioning
confidence: 67%
See 2 more Smart Citations
“…Previous studies have reported that many patients in OMT express a main goal of opioid abstinence (33,44,45). The before mentioned survey conducted by our research team, also discovered a high interest in XR-NTX treatment among OMT-patients (32). Since discontinuing substitution medication is risky even when patients are highly motivated, rather few succeed in detoxification from OMT and many relapse to opioid use (46).…”
Section: Retention In Treatmentmentioning
confidence: 67%
“…These participants (40.2%) reported more severe ongoing addiction-related problems compared to the participants recruited from the OMT-population, and were at higher risk of overdose due to their pattern of uncontrolled use of illicit substances (35). In a previous survey performed by our research group, opioid-dependent individuals not currently in OMT reported a higher interest in XR-NTX treatment than those enrolled in OMT (32). Thus, a number of opioid-dependent individuals whom for different reasons have chosen not to be enrolled in an available OMT treatment, have shown, both in attitude and in behaviour, attraction to XR-NTX treatment.…”
Section: Retention In Treatmentmentioning
confidence: 79%
See 1 more Smart Citation
“…The statements were scored using a 0-4 Likert scale from not interested (0) to very interested (4). For more information see Sharma Haase et al [28].…”
Section: Treatment Preferencementioning
confidence: 99%
“…However, there is no standardized or validated instrument for preference within SUD treatment [11]. The questions were designed to reflect the degree of commitment level to abstinence with naltrexone [28]. We assessed internal consistency for the 5 variables in terms of item-total correlations and Cronbach's alpha.…”
Section: Limitations and Strengthsmentioning
confidence: 99%